Ninth Five Year Plan (1997-2002) Draft Orissa Vol.-II - Planning Commission (Planning Commission, 1997)
GN. Statement (Abstract to Annexure-I), Draft Ninth Plan(1997-2002) and Annual Plan (1997-98)- Proposed Outlays, Physical Targets and Achievements, Proposals for Spillover and ongoing programmes/ Projects as in Annexure-I, Proposals for maximising benefits of completed programmes/Projects (as on 31.3.97).
Planning and Coordination Department, Government of Odisha